Analisis lingkungan kerja dan kompetensi dalam kinerja pegawai pada usaha jahit Linawaty Kebaya Medan - Sitepu, Astrid Sarah Dwyna B.; Sihombing, Marlon (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2023)
Linawaty Kebaya Sewing Business Medan is a sewing business that provides services in sewing clothes. This study aims to determine the influence of the work environment and competence on Linawaty Kebaya Sewing Business Medan. This study uses a qualitative research method with a descriptive research type. Primary data collection techniques through interviews with several informants at Linawaty Kebaya Sewing Business Medan and observation. For secondary data collection through literature studies and documentation. The data analysis process is carried out by collecting data, reducing data, presenting data and drawing conclusions. The results of this study indicate that the work environment and competence can improve the performance of Linawaty Kebaya Sewing Business Medan employees such as adequate lighting, sewing skills, punctuality in working on clothing products, building cooperation between fellow employees, the ability to follow developments regarding the latest fashion trends. However, there are several things that need to be considered in order to maintain employee performance. It can be concluded that the employees of Linawaty Kebaya Sewing Business have different motivations but have the same goal to make Linawaty Kebaya Sewing Business Medan better than before.